Pengaruh Marketing Mix Terhadap Keputusan Pembelian Kosmetik Wardah Di Samarinda - Nurfitriani, Rieni Angriani Eddy Soegiarto K (EKONOMIA, 2020)
The purpose of this study was to determine the effect of products, prices, distribution and promotion on purchasing decisions for wardah cosmetics in Samarinda. Theories used in this research are product, price, distribution and promotion. This research was conducted in samarinda city. Samples taken as many as 100 respondents with the Non Probability Sampling method with sampling techniques using purposive sampling.. Data collection by distributing questionnaires using a Likert scale to measure each indicator. The analytical tool in the study used multiple linear regression analysis using SPSS v23 program tools.The results of this study indicate that the product has a positive and significant effect on purchasing decisions for wardah cosmetics in Samarinda, prices have a positive and significant effect on purchasing decisions for wardah cosmetics in Samarinda, distribution has a positive but not significant effect on purchasing decisions for wardah cosmetics in Samarinda, promotions have a positive but not positive effect. significant influence on purchasing wardah cosmetics in Samarinda and the product, price, distribution and promotion together have a positive and significant effect on purchasing decisions of wardah cosmetics in Samarinda